Evaluation Of Special Education Curriculum At SLB Negeri Cileunyi - Ahmad Sukandar; Heri Mujianto; Iroh Nuraeni; Eulis Muplihati Sa’adah (Universitas Muhammadiyah Enrekang, 2022)
Evaluation is part of the management system, namely planning, organization, implementation, monitoring and evaluation. The curriculum is also designed from the planning stage, organization then implementation and finally monitoring and evaluation. Without evaluation, one will not know how the condition of the curriculum is in its design, implementation and results. The purpose of this research is to find out how the evaluation of the special education curriculum at the Cileunyi State SLB is. This type of research is qualitative research using qualitative methods, namely observation, interviews or document review. The results show that the Cileunyi State SLB school can be said to be an ideal school, by always evaluating the curriculum and innovative learning systems that arise as a result of the experiments of the school principal, teachers, and all the components in the Cileunyi State SLB, with proven graphs of an increase in new students every the year increases.